In Vivo Caprine Model for Osteomyelitis and Evaluation of Biofilm-Resistant Intramedullary Nails. (11th June 2013) - Tran, Nhiem; Tran, Phong A.; Jarrell, John D.; Engiles, Julie B.; Thomas, Nathan P.; Young, Matthew D.; Hayda, Roman A.; Born, Christopher T.
Abstract : Bone infection remains a formidable challenge to the medical field. The goal of the current study is to evaluate antibacterial coatings in vitro and to develop a large animal model to assess coated bone implants. A novel coating consisting of titanium oxide and siloxane polymer doped with silver was created by metal-organic methods. The coating was tested in vitro using rapid screening techniques to determine compositions which inhibited Staphylococcus aureus growth, while not affecting osteoblast viability. The coating was then applied to intramedullary nails and evaluated in vivo in a caprine model. In this pilot study, a fracture was created in the tibia of the goat, and Staphylococcus aureus was inoculated directly into the bone canal. The fractures were fixed by either coated (treated) or non-coated intramedullary nails (control) for 5 weeks. Clinical observations as well as microbiology, mechanical, radiology, and histology testing were used to compare the animals. The treated goat was able to walk using all four limbs after 5 weeks, while the control was unwilling to bear weight on the fixed leg. These results suggest the antimicrobial potential of the hybrid coating and the feasibility of the goat model for antimicrobial coated intramedullary implant evaluation.